Low light intensity and compost modified biochar enhanced maize growth on contaminated soil and minimized Pb induced oxidative stress (2021)
Heavy metal uptake by agricultural crops poses great danger to human health. Application of compost and biochar has been used extensively for metal immobilization in soil and to reduce metal uptake by crop plant. Their efficiency is however, limited by other environmental factors like water and light intensity. In this study, the effects of organic amendments (Mexican Sunflower Compost and Rice Husk (RH) biochar) in combination with varying light intensities on growth and Pb uptake by maize crop grown on industrially contaminated soil containing 53,752 mg/kg Pb was investigated. Compost and biochar were applied singly and in combination at 0, 2.5, 5 and 7.5 t ha􀀀1 while different layers of net were used to vary light intensity (one layer =60: 386 lx, two layers =53:340 lx, three layers =27 %: 177 lx and zero layer with 100 % light intensity of 634 lx served as control). Soil Pb concentration and stress metabolites (Proline and cysteine) production before and after the experiment were also determined. Results showed that, higher rates of organic amendments and reduced light intensity increased the vegetative growth and yield of maize on contaminated soil compared to 100 % light intensity. Combination of biochar and compost performed better than sole application. It reduced post-cropping soil Pb concentration and Pb uptake by maize, especially under low light intensity. The stress metabolites were more in the leaves of maize crop grown in un-amended soil and under 100 % light intensity. Addition of organic amendment coupled with reduction in light intensity therefore, enhanced maize growth on contaminated soil, reduced Pb uptake and oxidative stress, while, heavy metal accumulation and stress metabolites production were more in maize grown in un-amended soil and exposed to high light intensity.